2004
DOI: 10.1364/ao.43.000608
|View full text |Cite
|
Sign up to set email alerts
|

Measurement accuracy in control of segmented-mirror telescopes

Abstract: Design concepts for future large optical telescopes have highly segmented primary mirrors, with the out-of-plane degrees of freedom actively controlled. We estimate the contribution to errors in controlling the primary mirror that results from sensor noise and, in particular, compare mechanical measurements of relative segment motion with optical wave-front information. Data from the Keck telescopes are used to obtain realistic estimates of the achievable noise due to mechanical sensors. On the basis of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 10 publications
(21 reference statements)
0
16
0
Order By: Relevance
“…The propagation of sensor noise is understood [3,10], and while this may limit the desired control bandwidths, it does not otherwise affect the feedback problem.…”
Section: A Segmented-mirror Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The propagation of sensor noise is understood [3,10], and while this may limit the desired control bandwidths, it does not otherwise affect the feedback problem.…”
Section: A Segmented-mirror Controlmentioning
confidence: 99%
“…The next smallest nonzero singular values, corresponding to astigmatism, scale roughly as 2:5=N; these scalings can both be verified by construction using the formulas in [3]; the astigmatism scaling also follows from Eq. (6) in [10]. Even for the relatively large sensor moment arm at Keck of L eff ¼ 55 mm, focus mode will have the smaller sensitivity for any telescopes currently being designed.…”
Section: A Segmented-mirror Controlmentioning
confidence: 99%
“…We considered this question in detail elsewhere 19,20 and concluded that a supplementary wave-front sensor is not likely to be needed for stabilization purposes. Here we just summarize the argument.…”
Section: Error Multipliers From Singular-value Decompositionmentioning
confidence: 99%
“…For realistic choices of dihedral sensitivity, focus-mode remains the least-observable deflection pattern (smallest singular value) after global piston, tip, and tilt. The next least-observable modes (relatively large ratio of rms surface motion to resulting rms edge discontinuity [9]) are spatially smooth and similar to Zernike basis functions. The full interaction matrix relates all three displacements at the sensor location (height combined with dihedral, gap, and shear) to all six possible rigid-body deflections of each mirror segment.…”
Section: A Descriptionmentioning
confidence: 83%